2015
DOI: 10.1021/tx5005002
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Reaction Products with a Chemical Allergen, Methylene-diphenyl Diisocyanate, Stimulate Alternative Macrophage Activation and Eosinophilic Airway Inflammation

Abstract: Isocyanates have been a leading chemical cause of occupational asthma since their utility for generating polyurethane was first recognized over 60 years ago, yet the mechanisms of isocyanate asthma pathogenesis remain unclear. The present study provides in vivo evidence that a GSH mediated pathway underlies asthma-like eosinophilic inflammatory responses to respiratory tract isocyanate exposure. In naïve mice, a mixture of GSH reaction products with the chemical allergen, methylene-diphenyl diisocyanate (MDI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 55 publications
7
43
0
Order By: Relevance
“…Additional staining was also noted in cells that resemble alveolar macrophages, consistent with data from studies of BAL cells shown in Figure 2. The data validate the recently described effectiveness of delivering reactive MDI to the lower airways in rodents, via intranasal application of reversibly reactive MDI-GSH conjugates (Wisnewski, Liu et al 2015). …”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Additional staining was also noted in cells that resemble alveolar macrophages, consistent with data from studies of BAL cells shown in Figure 2. The data validate the recently described effectiveness of delivering reactive MDI to the lower airways in rodents, via intranasal application of reversibly reactive MDI-GSH conjugates (Wisnewski, Liu et al 2015). …”
Section: Resultssupporting
confidence: 86%
“…The present immunocytochemical studies with anti-MDI polyclonal antiserum expand upon recent studies demonstrating the capacity of reversibly reactive MDI-GSH conjugates to induce eosinophilic airway inflammation in sensitized animals (Wisnewski, Liu et al 2015). The data confirm penetration of MDI to the lower airways following intranasal application of MDI-GSH conjugates under light anesthesia; unlike prior studies, which have found limited lower airway penetration of pure isocyanate vapors (or solutions in organic solvent), presumably due to the scrubbing effects of rodent upper airways (Kennedy, Singh et al 1993, Kennedy, Wilson et al 1994, Pauluhn 2014).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Additional indications include CD14 gene polymorphism associations to diisocyanate asthma (Bernstein et al, 2011), and the finding that MDI-GSH reaction products induce e.g. the mouse chitinase YM-1 (Wisnewski et al, 2015). It has also been suggested that B1-lymphocytes, transferred from dermally TDI-sensitized mice, contribute to an innate-like rapid defense upon a TDI challenge in recipient mice (De Vooght et al, 2013).…”
Section: Discussionmentioning
confidence: 99%